Pre‐morbid type 2 diabetes mellitus is not a prognostic factor in amyotrophic lateral sclerosis. Issue 3 (1st June 2015) - Paganoni, Sabrina; Hyman, Theodore; Shui, Amy; Allred, Peggy; Harms, Matthew; Liu, Jingxia; Maragakis, Nicholas; Schoenfeld, David; Yu, Hong; Atassi, Nazem; Cudkowicz, Merit; Miller, Timothy M.
ABSTRACT Introduction: The aim of this study was to determine whether a history of pre‐morbid type 2 diabetes mellitus (DM2) is a prognostic factor in amyotrophic lateral sclerosis (ALS). Methods: The relationship between DM2 and survival was analyzed in a study population consisting of 1, 322 participants from 6 clinical trials. Results: Survival did not differ by diabetes status (log‐rank test, P = 0.98), but did differ by body mass index (BMI) (log‐rank test, P = 0.008). In multivariate analysis, there was no significant association between diabetes and survival (P = 0.18), but the risk of reaching a survival endpoint decreased by 4% for each unit increase in baseline BMI (HR 0.96, 95% CI 0.94–0.99, P = 0.001). DM2 was less prevalent among ALS clinical trial participants than predicted. Conclusions: A history of pre‐morbid DM2 is not an independent prognostic factor in ALS clinical trial databases. The low DM2 prevalence rate should be examined in a large, prospective study to determine whether DM2 affects ALS risk. Muscle Nerve 52:339–343, 2015